2017
DOI: 10.9790/0853-1601112325
|View full text |Cite
|
Sign up to set email alerts
|

Role of Pre And Postoperative Topical Cyclosporine (0.05%) on Recurrence in Recurrent And Vascularised Pterygium

Abstract: .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
2
1
Order By: Relevance
“…also showed no effect for CsA 0.05%, administered 4 weeks before and after surgery, on the recurrence rate (6% in the case and 8% in the control group). 19 However, the surgical technique (conjunctival limbal autograft with fibrin glue) and definition of the recurrence (any encroachment of conjunctiva >1 mm inside the limbus) were different in the study by Dhar from that in the present study, which could be another source of different rates reported. Other researchers reporting no effect for CsA have also used different inclusion criteria, such as bilateral pterygium with >2 mm corneal invasion.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…also showed no effect for CsA 0.05%, administered 4 weeks before and after surgery, on the recurrence rate (6% in the case and 8% in the control group). 19 However, the surgical technique (conjunctival limbal autograft with fibrin glue) and definition of the recurrence (any encroachment of conjunctiva >1 mm inside the limbus) were different in the study by Dhar from that in the present study, which could be another source of different rates reported. Other researchers reporting no effect for CsA have also used different inclusion criteria, such as bilateral pterygium with >2 mm corneal invasion.…”
Section: Discussioncontrasting
confidence: 71%
“… 16 However, the results of the studies are controversial in this regard, and some have suggested no significant effect for CsA on recurrence rate. 17 18 19 20 We aimed to evaluate the efficacy of 3-month administration of topical CsA 0.05% on postoperative recurrence after pterygium surgery. Accordingly, in the present study, we selected pterygium cases undergoing the rotational conjunctival autograft technique plus MMC and compared the efficacy of adjunctive therapy with CsA on the postoperative outcomes, including prevention of pterygium recurrence, inflammation, and complications compared with the control group.…”
Section: Introductionmentioning
confidence: 99%
“…(3.4%), but lower than observed by Tok et al (12.9%) 17 . It may be higher than observed by Aydin et al because of the study population of only vascularized and recurrent pterygium, which is more prone for higher recurrence compared to primary pterygium 20 .…”
Section: Pak J Ophthalmolmentioning
confidence: 53%